Methoxylation of alpha-pinene over polymeric catalytic membranes containing sulfonic acid groups - Castanheiro, J (2012)
In this study, poly(vinyl alcohol) (PVA) membranes were prepared using sulfosuccinic acid (SSA) by varying the amount of SSA (5-40 mol%) and were used for the methoxylation of a-pinene. The absorption band at 1037 cm-1 in the FTIR spectrum of PVA_SSA40 (PVA membrane containing 40% of –OH groups esterified with SSA) which does not appear in the spectrum of PVA, indicates the presence of the sulfonic acid groups. The conversion of a-pinene increases when the amount of sulfosuccinic acid used in the polymer crosslinking is increased from 5% to 40%. However, when the crosslinking degree increases from 20% to 40%, the conversion of a-pinene increases only slightly. Good values of selectivity to a-terpinyl methyl ether were obtained with poly(vinyl alcohol) anchored sulfonic acid groups. Catalytic stability of the PVA_SSA40 was evaluated by performing consecutive batch runs with the same catalyst sample. After the third batch it was observed a stabilisation of the initial activity.